Algorithmic culture, networked learning and the technological horizon of theory. Issue 4 (8th August 2019) - Dawson, Mark
ABSTRACT: Going via Bernard Stiegler's theorisation of technology, and his response to Chris Anderson's claim that the era of hyper-networked, algorithmically driven digital technologies signals the end of theory, this paper aims to place the educational practice of networked learning as a space to think the edge, excess or limit of this proposed algorithmic dominance. The author discusses how networked learning can negotiate the border between educational theory, the practice of teaching and learning, and the processes and systems of educational technology, but suggests that to do this it must engage these disciplines through a thinking of technology which does not decide upon its status in advance. He argues that affirming this particular relation to technology is increasingly urgent given we are at a moment in which educational institutions are asking how to prepare our students for an age of continuing technological disruption.